Recensiones - Lolas Stepke, Fernando; Cornejo Plaza, María Isabel; Aguirre Salas, Jorge F.; Lavados Montes, Claudio (Acta Bioethica, 2013)
INTERACADEMY COUNCIL/IAP- THE GLOBAL NETWORK OF SCIENCE ACADEMIES, 2012 Responsible Conduct in the Global Research Enterprise: A Policy Report Fernando Lolas Stepke PIETRO MAGLIOZZI, M.I El arte de sanar María Isabel Cornejo Plaza LOLAS STEPKE, FERNANDO y DRUMOND, JOSÉ GERALDO DE FREITAS, editores Bioética Jorge F. Aguirre Salas LOLAS STEPKE, FERNANDO y DRUMOND, JOSÉ GERALDO DE FREITAS, editores Bioética Claudio Lavados Montes